Influence of the new standardized clinical cryopreservation/slow thawing protocol on immunogenicity of arterial allografts in rats - Hruby, Jan; Spunda, Rudolf; Mericka, Pavel; Mlcek, Mikulas; Pecha, Ondrej; Splith, Katrin; Schmelzle, Moritz; Krenzien, Felix; Lindner, Jaroslav; Spacek, Miroslav; Matia, Ivan (PloS one, 2020)
OBJECTIVES AND DESIGN: At the present time there are two waiting list for patients with vascular prosthetic infection indicated for arterial transplantation in the Czech Republic. The inclusion of each patient for cold-stored or cryopreserved arterial transplantation is the preference of indicating surgeon. In this experimental work we studied the immunogenicity of rat aortal allografts treated by our new clinical cryopreservation/slow thawing protocol. MATERIAL AND METHODS: Brown-Norway (BN) (N = 6, 203-217 g) or Lewis (LEW) (N = 6, 248-254 g) abdominal aortal grafts treated in accordance with our new clinical cryopreservation/slow thawing protocol were orthotopically transplanted to Lewis recipients (N = 12, 191-245 g). Aortal wall histology and infiltration by recipient immune cells, as well as donor specific anti MHC class I and II antibodies in recipient serum were studied in both isografts and allografts on day 30 postransplant. Core data of cryopreserved allografts were compared to our previous data of cold-stored aortal allografts treated in accordance with our clinical cold-storage protocol. RESULTS: Cryopreserved allografts showed regular morphology of aortal wall with clear differentiation of all three basic anatomical layers on day 30 postransplant. Intimal layer showed no hyperplasia, luminal surface was covered by endothelial cells. No statistical difference was observed in tunica media thickness between isografts and allografts. The medial layer showed no necrosis, shrinkage or immunoglobuline G deposition in any experimental group. The adventitial infiltration by immune cells was significantly higher (P<0.05) in allografts. Cryopreserved allografts showed significant lower activation of both cell- and antibody mediated immunity compared to historical data of cold-stored allografts. CONCLUSION: Aortal wall histology of rat allografts treated by our new standardized clinical cryopreservation/slow thawing protocol was comparable to that of the cryopreserved isografts on day 30 posttranspant. The immunogenicity of cryopreserved aortal allografts was significantly lower compared to that of cold-stored aortal allografts.
Keywords: kryoprezervace; aorta; Cryopreservation; potkani inbrední BN; Rats, Inbred Lew; Graft Rejection; krysa rodu Rattus; modely u zvířat; alografty; zvířata; Transplantation, Homologous; Rats, Inbred BN; arterie; Arteries; Male; Czech Republic; potkani inbrední LEW; Models, Animal; Rats; Allografts; Animals; Česká republika; mužské pohlaví; homologní transplantace; Aorta; rejekce štěpu